2022
DOI: 10.1186/s12889-022-12504-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of death causes of residents in poverty-stricken Areas in 2020: take Liangshan Yi Autonomous Prefecture in China as an example

Abstract: Background Continuous surveillance of death can measure health status of the population, reflect social development of a region, thus promote health service development in the region and improve the health level of local residents. Liangshan Yi Autonomous Prefecture was a poverty-stricken region in Sichuan province, China. While at the end of 2020, as the announcement of its last seven former severely impoverished counties had shaken off poverty, Liangshan declared victory against poverty. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Our study findings indicated a declining trend in all-cause mortality among older adults in China from 2009 to 2019, with male mortality rates generally being higher than female mortality rates. A study conducted in Liangshan Yi Autonomous Prefecture in China showed that the male mortality rate was approximately 1.47 times higher than the female mortality rate, and a study in the United States also reported higher male mortality rates [ 12 , 13 ]. These findings are likely to be associated with different lifestyles among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings indicated a declining trend in all-cause mortality among older adults in China from 2009 to 2019, with male mortality rates generally being higher than female mortality rates. A study conducted in Liangshan Yi Autonomous Prefecture in China showed that the male mortality rate was approximately 1.47 times higher than the female mortality rate, and a study in the United States also reported higher male mortality rates [ 12 , 13 ]. These findings are likely to be associated with different lifestyles among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Improving health literacy is one of the most fundamental, economical and effective measures to improve health level of the whole people. Liangshan Prefecture declared comprehensive poverty alleviation at the end of 2020 [ 42 ], but the health literacy of residents in Liangshan Prefecture is still extremely low. Increasing the health literacy level of Liangshan Prefecture residents as soon as possible is an important measure to consolidate the achievement of poverty alleviation.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40% of them lost at least one of their parents, according to a survey conducted among 328 Yi children in 2009 [34]. Experiences of parental loss among Yi young people are primarily due to poor health and unexpected injuries/fatalities in the hazardous mountainous region [34,35]. In earlier years, the high incidence of HIV/AIDS infection in Liangshan was also a contributing factor [36][37][38].…”
Section: Context Of This Research: the Case Of The Yi Ethnic Minority...mentioning
confidence: 99%